2019
DOI: 10.1002/dvdy.124
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary approach to investigate collective cell migration in neural crest

Abstract: The neural crest serves as a powerful and tractable model paradigm for understanding collective cell migration. The neural crest cell populations are well‐known for their long‐distance collective migration and contribution to diverse cell lineages during vertebrate development. If neural crest cells fail to reach a target or populate an incorrect location, then improper cell differentiation or uncontrolled cell proliferation can result. A wide range of interdisciplinary studies has been carried out to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…Theoretical models can be a powerful tool to investigate and identify the cues that drive collective migration and rearrangement. For instance, modeling studies have been used to identify key cues that govern the collective behavior of neural crest cell migration (Giniūnaitė, Baker, et al, 2020; Giniūnaitė, McLennan, et al, 2020; Shellard & Mayor, 2020), cancer cell invasion (George et al, 2017; Stichel et al, 2017), bacterial swarming (Jeckel et al, 2019; Peruani et al, 2012) and collective animal behaviors (Giardina, 2008). We believe that theoretical modeling can be employed to bridge the gap between the microscopic and macroscopic scales and advance our understanding of how collective behaviors drive the emergence of macroscopic features such as vascular network morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical models can be a powerful tool to investigate and identify the cues that drive collective migration and rearrangement. For instance, modeling studies have been used to identify key cues that govern the collective behavior of neural crest cell migration (Giniūnaitė, Baker, et al, 2020; Giniūnaitė, McLennan, et al, 2020; Shellard & Mayor, 2020), cancer cell invasion (George et al, 2017; Stichel et al, 2017), bacterial swarming (Jeckel et al, 2019; Peruani et al, 2012) and collective animal behaviors (Giardina, 2008). We believe that theoretical modeling can be employed to bridge the gap between the microscopic and macroscopic scales and advance our understanding of how collective behaviors drive the emergence of macroscopic features such as vascular network morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Neural crest migration offers a natural application within developmental biology, and more widely provides a paradigm system for studying cell invasion. One integrated experimentaltheoretical approach has focussed on chick cranial neural crest cell migration, suggesting a process in which cells follow a vascular endothelial growth factor (VEGF) attractant gradient selfgenerated through their uptake of VEGF [2]. An agent-based modelling approach suggested that distinct cell phenotypes (termed "leaders" and "followers") were required for successful migration, differing (amongst other factors) in their response to the gradient of VEGF [2].…”
Section: Discussion and Research Perspectivesmentioning
confidence: 99%
“…One integrated experimentaltheoretical approach has focussed on chick cranial neural crest cell migration, suggesting a process in which cells follow a vascular endothelial growth factor (VEGF) attractant gradient selfgenerated through their uptake of VEGF [2]. An agent-based modelling approach suggested that distinct cell phenotypes (termed "leaders" and "followers") were required for successful migration, differing (amongst other factors) in their response to the gradient of VEGF [2]. While these agent-based models have been extended to include a continuous spectrum of phenotypes [44],…”
Section: Discussion and Research Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute the deviations of the dynamics and morphological outcomes of the multicellular masses from generic physical predictions to the contribution of agent-like behaviors, e.g., directed migration, regulated quiescence, oscillatory signal relay, of the cells themselves. Cells of clonally developing multicellular organisms can also exhibit agent-like behaviors [ 171 173 ]. While it is difficult to quantify the relative contributions that each class of phenomena makes to the respective developmental processes, we suggest that morphogenesis of Myxobacteria and Dictyostelia is more dependent on agent-like behaviors than that of animals or plants.…”
Section: Discussionmentioning
confidence: 99%